The impact of prolapse mesh on vaginal smooth muscle structure and function. (20th August 2015) - Jallah, Z; Liang, R; Feola, A; Barone, W; Palcsey, S; Abramowitch, SD; Yoshimura, N; Moalli, P
Abstract : Objective: To evaluate the impact of prolapse meshes on vaginal smooth muscle structure (VaSM) and function, and to evaluate these outcomes in the context of the mechanical and textile properties of the mesh. Design: Three months following the implantation of three polypropylene prolapse meshes with distinct textile and mechanical properties, mesh tissue explants were evaluated for smooth muscle contraction, innervation, receptor function, and innervation density. Setting: Magee‐Womens Research Institute at the University of Pittsburgh. Population: Thirty‐four parous rhesus macaques of similar age, parity, and pelvic organ prolapse quantification (POP–Q) scores. Methods: Macaques were implanted with mesh via sacrocolpopexy. The impact of Gynemesh ™ PS (Ethicon; n = 7), Restorelle ® (Coloplast; n = 7), UltraPro ™ parallel and UltraPro ™ perpendicular (Ethicon; n = 6 and 7, respectively) were compared with sham‐operated controls ( n = 7). Outcomes were analysed by Kruskal–Wallis ANOVA, Mann–Whitney U –tests and multiple regression analysis ( P < 0.05). Mean outcome measures: Vaginal tissue explants were evaluated for the maximum contractile force generated following muscle, nerve, and receptor stimulation, and for peripheral nerve density. Results: Muscle myofibre, nerve, and receptor‐mediated contractions were negatively affected by mesh only in the grafted region ( P < 0.001, P = 0.002, and P = 0.008, respectively), whereas cholinergic and adrenergic nerve densities were affected in the grafted ( P = 0.090 and P = 0.008, respectively) and non‐grafted ( P = 0.009 and P = 0.005, respectively) regions. The impact varied by mesh property, as mesh stiffness was a significant predictor of the negative affect on muscle function and nerve density ( P < 0.001 and P = 0.013, respectively), whereas mesh and weight was a predictor of receptor function ( P < 0.001). Conclusions: Mesh has an overall negative impact on VaSM, and the effects are a function of mesh properties, most notably, mesh stiffness. Tweetable abstract: Prolapse mesh affects vaginal smooth muscle. Tweetable abstract: Prolapse mesh affects vaginal smooth muscle.